Strengthening digital capital on social media for collective social action in micro, small, and medium enterprises (MSMEs) - Prayoga, Reza Amarta; Wijaya, Gustaf; Fitriyah, Neka; Wicaksono, Arditya; Wahyono, Eko (Bricolage : Jurnal Magister Ilmu Komunikasi, 2024)
The development potential of local superior products, especially MSMEs, needs to be transformed into digital businesses. Expanding market reach is an important step to help MSMEs survive the national economic crisis caused by COVID-19. Adaptation to the digital economy at the marketplace is a curative solution to the problem of the community's economic downturn. This study aims to examine community interventions in empowering MSME entrepreneurs through the utilization of digital capital, digital marketing of superior local products, and collective social action models through multi-platform market ecosystems. A qualitative method with a phenomenological approach was used, involving data collection through interviews, observations, and literature studies. A total of 10 informants were involved as data sources. The results show that digital capital is essential for capacity that must be internalized and intervened by businesses in transforming into digital businesses. Digital capital empowerment involves a Community-Based Local Product (CBLP) approach, which is the involvement of local communities with digital skills and competencies in local product development. This includes design, management of digital resources and products, decision-making, and profit sharing, based on the principle of equality for MSME players.